KEPADATAN INDIVIDU KLAMPIAU (Hylobates muelleri) DI JALUR INTERPRETASI BUKIT BAKA DALAM KAWASAN TAMAN NASIONAL BUKIT BAKA BUKIT RAYA KABUPATEN MELAWI - to, Aris; Nurdjali, Bachrun; Herawatiningsih, Ratna (Universitas Tanjungpura, 2014)
Bornean Gibbon (Hylobates muelleri) is one primate species protected under wildlife protection laws Number 266 of 1931 and Forestry Minesterial Decree Number 5/Kpts-II/1991 dated 10 June 1991 and law number 5 of 1990. Baka hill is protected areas in West Borneo within the territory of the National Park Bukit Baka Bukit Raya the habitat of bornean gibbon. This study aims to determine the number of individuals and individuals density of bornean gibbon in lines interpretation baka hill in the region Bukit Baka Bukit Raya National Park Melawi District. Number of individuals were found at the time of the study with 6 lanes and 3 replication by 99 individuals with a mean number of individuals bornean gibbon at 33,0001 individuals. Results of data analysis on a 95% confidence interval bornean gibbon individuals density lies between 0,4377 individuals/Ha to 0,6621 individuals/Ha. Whereas the 99% confidence interval bornean gibbon individual density lies between 0,3625 individuals/Ha to 0,7373 individuals/Ha. To the number of individuals per hectare with 95% confidence interval obtained by the number of individuals throughtout the area ranged from 5 to 6 tails. For a 99% confidence interval obtained by the number of individuals ranged from 4 to tails. Keyword: Density, individuals, Bornean Gibbon, Bukit Baka Bukit Raya National Park.